Evaluation of Physics Frameworks for Building Web-Based Games - Resa Yogya; Raymond Kosala (Journal of Games, Game Art, and Gamification, 2016)
Recently, WebGL technology has shown a lot of potential for developing games. Since this technology is still relatively new, there is still much potential in the game development area that has not been explored yet. This paper explores the development of a game engine made with WebGL technology that integrates some physics frameworks for developing web-based 2D or 3D games. Specifically, we integrated three open source physics frameworks, which are Bullet, Cannon, and JigLib, into a WebGL-based game engine. We assessed these frameworks using some experiments, in terms of their correctness or accuracy, performance, completeness and compatibility. The results show that it is possible to integrate open source physics frameworks into a WebGL-based game engine, and Bullet is the best physics framework to be integrated into a WebGL-based game engine.